ANALISIS KEINDAHAN HURUF NIDA’ DALAM AL-QUR’AN SURAT HUD JUZ 11-12 (Kajian Ilmu Nahwu dan Balaghah): Indonesia - Inayatul Udhia; Iis Maisaroh; Muhtarom (STIT Pringsewu, 2022)
Abstract Disciplines of linguistic knowledge such as nahwu and balaghah will help and facilitate the reviewers of the Qur'an in understanding the values contained and the linguistic rules in it. This study has a problem formulation including what are the types of an-nida, how is i'rob an-nida and how are the benefits of existencean-nida in the Qur'an Hud juz 11-12 according to the study of nahwu and balaghah science. The research approach used in this study is a qualitative descriptive approach. The research design used by the researcher is library research. Munada is the isim that is located after the letters an-nida. An-nida literally means calling with him. While an-nida according to the term is a request to face with the letter